Legal Effectiveness and Power Relations in Implementing Campus Sexual Violence Prevention Policies - Henny Wijayanti; Puan Dinaphia Yunan; Arovah Windiani; Gamalel Rifqi Samhudi; Mansur (Nusantara: Journal of Law and Islamic Law, 2026)
This sociological and legal study evaluates the implementation of Universitas Muhammadiyah Jakarta Rector Regulation Number 918 A of 2021 concerning campus sexual violence prevention. Despite progressive normative frameworks, violence remains a critical educational issue. This qualitative research employs purposive sampling with five hundred respondents, utilizing the legal effectiveness theory alongside the power relations analysis of Michel Foucault. The findings reveal that current policy implementation is suboptimal due to inadequate reporting facilities, minimal socialization, and an entrenched patriarchal legal culture. Furthermore, asymmetrical power relations between lecturers and students create deeply coercive disciplinary environments. This hierarchical dominance silences victims, fosters victim blaming, and significantly reduces vital institutional trust. Consequently, universities often prioritize institutional shielding over comprehensive victim rehabilitation. In conclusion, mitigating campus sexual violence requires far more than mere normative texts; it absolutely demands systemic reconstruction of specialized task forces, anonymous digital reporting infrastructures, and total eradication of abusive academic power dynamics.